Persistent Urogenital Membrane in Femaie Children Over tie Vaginal Vestibule - Yodava, V. N. S.; Tiwari, V. S. (Indian Journal of Plastic Surgery, 1977)
This article consists of seven female children with alike congenital problem creating great psychological set back to their parents. The children had persistant urogenital membrane in vestibular area except with a very small opening for urinar; passage. This being a rare congenital anomaly with its very simple technique of its cure, to relieve the mental worry of the parents, prompted us to put this in the literature for further exploration of its etiology and existence.